MICROFACIES OF LATE PLEISTOCENE TRAVERTINE DEPOSITS IN JORDAN - Makhlouf, Issa Mohammad; Ibrahim, Khalil M; El Naqah, Ali R; Al-Thawabteh, Sana’ M. (Malaysian Journal of Science, 2022)
The Late Pleistocene travertine outcrops from Deir Alla, Suwayma, and Az Zara were investigated, and their microfacies were identified. The microfacies of the Deir Alla travertines include micrite and spar groundmass, shrubs, crystalline crusts, a stromatolite-like structure, peloids, and cements. Shrub travertine includes spar calcite-coated stems with probably microbial micritic clumps. The crystalline crust travertine displays an alternation of micrite and sparite laminae. The micritic laminae are dark-coloured. Bundles of radial spar crystals are associated locally with micritic groundmass. The crystalline crust developed where biogenic activity is limited. Peloidal microfacies are less than 0.25 mm in diameter, cryptocrystalline, pale-dark green in colour, elliptical to spherical in shape, and usually associated with microorganisms. The microfacies of the Suwayma and Az Zara travertines include crystalline calcite rhombs and other composite scalenohedral crystals. They occur as small anhedral-subhedral crystals, monocrystalline to some polycrystalline, corroded, subrounded, and mainly coated with iron oxide and/or clay minerals. Peloids, ooids, and oncoids are common. They are dark-green coloured, cryptocrystalline to microcrystalline carbonates of spherical and ellipsoidal shape with less than 1 mm in diameter. Rich flora travertines include reed and paper-thin rafts with leaf impressions encrusted on moss cushions. The flora observed in the upper part of the Suwayma section was identified as charophyte oospores (gyrogonites). A few grains of quartz are present as small subhedral-euhedral crystals, monocrystalline, corroded, rounded, and mainly coated with iron oxide. The iron is irregularly distributed among the laminae and voids and is occasionally replaced by carbonates. The described macrophyte encrustation structures probably represent algae, cyanobacteria, or bryophytes. All samples of micrite and spar calcite appear as groundmass.